CXCL8 is a potential biomarker for predicting disease progression in gastric carcinoma - Qi, Wen-Qian; Zhang, Qian; Wang, Jiang-Bin (Translational Cancer Research; Vol 9, No 2 (February 28, 2020): Translational Cancer Research, 2020)
Background: To find potential biomarkers for predicting disease progression in gastric cancer (GC). Methods: An extensive bioinformatics study of the Cancer Genome Atlas (TCGA) and Oncomine datasets was conducted to define potential mRNA biomarkers for GC. The mRNA expression profiles of 375 GC and 32 neighboring noncancerous adrenal tissues were analyzed. The Oncomine database was used to validate the hub genes. The correlation between candidate hub gene expression and survival of GC patients was analyzed using the Kaplan-Meier method. Results: Ten differentially expressed genes were identified as hub genes, and CXCL8 was the only gene validated as being up-regulated in GC tissues compared to control tissues using both the TCGA and Oncomine databases. Immunofluorescence staining showed that CXCL8 was expressed in GC tissues, and its higher expression predicted worse relapse-free survival in GC patients. Conclusions: CXCL8 is a potential biomarker for predicting disease progression in GC.